New voices in Arab cinema - Armes, Roy (Indiana University Press, 2015)
"New Voices in Arab Cinema focuses on contemporary filmmaking since the 1980s, but also considers the longer history of Arab cinema. Taking into consideration film from the Middle East and North Africa and giving a special nod to films produced since the Arab Spring and the Syrian crisis, Roy Armes explores themes such as modes of production, national cinemas, the role of the state and private industry on film, international developments in film, key filmmakers, and the validity of current notions like globalization, migration and immigration, and exile. This landmark book offers both a coherent, historical overview and an in-depth critical analysis of Arab filmmaking."--Back cover